2005
DOI: 10.1080/02643290500200122
|View full text |Cite|
|
Sign up to set email alerts
|

Non-random associations of graphemes to colours in synaesthetic and non-synaesthetic populations

Abstract: This study shows that biases exist in the associations of letters with colours across individuals both with and without grapheme-colour synaesthesia. A group of grapheme-colour synaesthetes were significantly more consistent over time in their choice of colours than a group of controls. Despite this difference, there were remarkable inter-subject agreements, both within and across participant groups (e.g., a tends to be red, b tends to be blue, c tends to be yellow). This suggests that grapheme-colour synaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
314
4
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 251 publications
(371 citation statements)
references
References 30 publications
47
314
4
6
Order By: Relevance
“…Given this, we can conclude that broad sound symbolic rules contribute, at least to some extent, to the formation of JIW's word-flavour associations. Our study provides additional support for the existing literature suggesting that synaesthesia is an exaggeration or heightened consciousness of rule-guided cross-modal associations present in the general public (e.g., Beeli, Esslen, & Jancke, 2007;Simner et al, 2005). However, we have also provided information about the very nature of sound symbolism, using evidence from synaesthesia.…”
Section: Discussionsupporting
confidence: 67%
“…Given this, we can conclude that broad sound symbolic rules contribute, at least to some extent, to the formation of JIW's word-flavour associations. Our study provides additional support for the existing literature suggesting that synaesthesia is an exaggeration or heightened consciousness of rule-guided cross-modal associations present in the general public (e.g., Beeli, Esslen, & Jancke, 2007;Simner et al, 2005). However, we have also provided information about the very nature of sound symbolism, using evidence from synaesthesia.…”
Section: Discussionsupporting
confidence: 67%
“…In other words, semantic radicals appear to have most influence on synaesthetic colouring when they sit in their most frequent, optimal position. Linguistic frequency has also been shown to influence synaesthetic colouring in a number of other ways for English synaesthetes (Simner & Ward, 2008;Simner et al, 2005;Smilek et al, 2007), as well as other European language speaking synaesthetes (e.g., German; see Beeli et al, 2007);. Our present findings appear to extend this to Chinese synaesthetes.…”
Section: Discussionsupporting
confidence: 76%
“…As such, we encourage future research to investigate again these effects against the level of fluency of speakers. Future research might also test Chinese nonsynaesthetes as controls to establish whether the intuitions of non-synaesthetes mirror those of genuine synaesthetes, as has been found in other studies (e.g., Simner et al, 2005).. In summary, we have shown that the colour of left-right compound characters is significantly closer to certain radical types over others, according to their function and position.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations